The Influence of Cross-Generational Leadership Styles on the Performance of Generation Z Employees Through Employee Engagement, Job Satisfaction, and Organizational Culture as Intervening Variables in the Coal Mining Industry at PT Khotai Makmur Insan Abadi Kutai Kartanegara - Fitri Windasari; Gurawan Dayona Ismail; Ridlwan Muttaqin; Pras Rendy; Irving Ignatius Paul Luntungan (Eduvest - Journal of Universal Studies, 2026)
Employee performance refers to the level of success achieved by employees in completing their tasks, as reflected in the quality and quantity of work outcomes according to their roles, responsibilities, and organizational standards. This study aims to examine the effect of leadership styles on Generation Z employee performance, with employee engagement, job satisfaction, and organizational culture as intervening variables. The research employed a quantitative method with descriptive and verification approaches. The data sources consisted of primary and secondary data. Data were collected through interviews, questionnaires, and observations from a population of 135 employees. The sampling technique used was non-probability sampling with a purposive sampling method. The analytical tools used in this study were SPSS 25 for descriptive analysis and SmartPLS 4 for verification analysis. The measurement model (outer model) was evaluated using convergent validity, discriminant validity, Average Variance Extracted (AVE), composite reliability, and Cronbach’s alpha. The structural model (inner model) was assessed using the coefficient of determination (R²) and predictive relevance (Q²). The results showed that leadership styles had positive and significant effects on employee engagement, job satisfaction, and organizational culture. Employee engagement and job satisfaction significantly influenced employee performance, whereas leadership styles and organizational culture did not have a direct significant effect on employee performance. Furthermore, organizational culture did not mediate the relationship between leadership styles and employee performance. In contrast, employee engagement and job satisfaction successfully mediated the effect of leadership styles on employee performance.